Peningkatan Pengetahuan Tentang Stunting pada Ibu Balita di Kelurahan Pondok Ranggon Cipayung Jakarta Timur Provinsi DKI Jakarta - Yeny Sulistyowati; Lili Indrawati; Suryani Suryani; Sukma Aditya Putra; Muhammad Gumilar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Stunting in early life, especially in the first 1000 days from conception to the age of two years, impaired growth has adverse functional consequences in children. The current condition of the COVID-19 pandemic requires more and more multi-sectoral collaboration to prevent these consequences. Some of these consequences include poor cognition and educational performance, poor parenting, low adult wages, lost productivity, and accompanied by excessive weight gain later in life, an increased risk of chronic nutrition-related diseases in adult life. Mother's knowledge of toddlers also plays a role in this effort. Therefore, the purpose of this activity is to increase the knowledge of mothers under five about stunting. The activity was carried out in several Posyandu areas which was carried out in September – October 2022. The implementation was in collaboration with Cadres, Pondok Ranggon Village Health Center, Cipayung District Health Center and Pondok Ranggon Village and Cipayung District. The result of this activity is an increase in partner empowerment through increased knowledge (Post Test Results Increase compared to Pre Test) namely those whose knowledge is good from 95% to 98% after counseling and increasing partner skills (Cross-program collaboration, evidenced by the active involvement of community elements (Village government, RW, cadres, youth organizations and religious leaders.) With the increase in knowledge of mothers and children under five, it is hoped that the role of cooperation with cross-sectors will be increased so that the sustainability of the program can be well maintained. Keywords: Knowledge, Mother, Children Under Five, Stunting